STRATEGY OF TRANSLATION IN NEWS BROADCAST ON TELEVISION FOR STUDENTS - Istiana Deni Putri (Corolla International Conference, 2022)
The purpose of this study is to see how students perform when they watch television and come across news broadcast in English that they then try to translate into Indonesian. News broadcast is an activity to spread or broadcast information about an event or incident which is then shared on television or radio shows. It can be used as a learning tool during the Covid-19 pandemic. It contains a variety of information. In this case, students are expected to be accountable for the portion of the words they heard. Students may be unaware that the news they are watching is the result of a translation because the translator pays attention to the language style and presentation method, which is similar to domestic news. This demonstrates that the news translation is of high quality. Accuracy and focus are required when listening to and remembering words in sentences. Because if it is one of the letters, it will result in a translation error. News broadcasts on the Metro Tv channel are an option in this study. Because Metro Tv has broadcast hours dedicated to broadcasting news in English. The goal of this research is to identify the best strategy for ensuring the success of translation activities. Several strategies will be attempted to be applied to students who focus on student activeness when: 1.) Analyzing words, 2.) Writing words, and 3.) Translating in their native language. This time, the researchers hope that students will be able to understand what strategies they use to produce high- quality results based on aspects such as accuracy, acceptability, readability, and ease of understanding or re-learning.